Impacts of aphid herbivory on mycorrhizal growth responses across three cultivars of wheat. Issue 6 (1st August 2022) - Charters, Michael D.; Durant, Emily K.; Sait, Steven M.; Field, Katie J.
Abstract : Societal Impact Statement: The Earth's population is projected to rise to 9.7 billion by 2050 resulting in mounting pressure to increase agricultural yields in a sustainable manner. Arbuscular mycorrhizal (AM) fungi may be important players in this agricultural transition given their capacity to improve soil and plant health. Benefits gained by crops hosting AM fungi can be cultivar‐specific and also affected by insect herbivory, although the combined effect of these factors remains unclear. Here, we show that, in an economically and socially significant tri‐partite system, there is interplay between crop cultivar, AM colonisation and aphid herbivory on plant growth and nutritional status. Summary: Arbuscular mycorrhizal (AM) fungi are critical components of the rhizosphere across nearly all terrestrial biomes. AM fungi associate with most plants, including major crops,  usually increasing plant access to soil nutrients and enhancing defence against pests and pathogens in return for photosynthetic carbon (C). However, plant growth responses to AM fungi vary according to species and genotype, an issue pertinent in agro‐ecosystems where crop cultivar can play an important role in AM function. Evidence suggests other biotic interactions, including with sap‐feeding aphids, impact the function of AM symbioses in plants. Nonetheless, whether these biotic factors alter genotype (or cultivar)‐specific plant growth and nutritional responses to colonisation by AM fungi remains unclear. Here, we investigated whether mycorrhizal responsiveness of three cultivars of wheat ( Triticum eastivum L.) to colonisation by a ubiquitously occurring AM fungus ( Rhizophagus irregularis ) differ in the presence or absence of bird cherry‐oat aphids ( Rhopalosiphum padi ), a major pest of cereals. Our findings show that although AM fungal colonisation and AM‐mediated plant growth responses were not affected by aphid feeding, there was variation between cultivars in the benefits gained by host plants in terms of nutrient acquisition and root growth, while aphid abundances also differed between wheat varieties. Understanding what causes cultivar‐specific outcomes and how they ultimately impact plant growth promotion, crop yields and food production represent key future research goals in agroecology. Abstract : The Earth's human population is projected to rise to 9.7 billion by 2050 resulting in mounting pressure to increase agricultural yields in a sustainable manner. Arbuscular mycorrhizal (AM) fungi may be important players in this agricultural transition given their capacity to improve soil and plant health. Benefits gained by crops hosting AM fungi can be cultivar‐specific and also affected by insect herbivory, although the combined effect of these factors remains unclear. Here, we show that, in an economically and socially significant tri‐partite system, there is interplay between crop cultivar, AM colonisation and aphid herbivory on plant growth and nutritional status.